A case study: emerging role of telehealth and local health practitioners during COVID-19 pandemic - Husain, Absar; Akinola, Ajoke; Akhtar, S. M. (International Journal Of Community Medicine And Public Health, 2021)
This case study investigates the experiences of planning and strategies to respond to a medical emergency and healthcare delivery during the COVID-19 pandemic, the local health practitioners from rural and urban areas of northern India; we included the experiences of telemedicine among the practitioners of Allopathic medicine System, Indian medicine System, and Allied health services. The case study recorded descriptive telephonic interviews about the situation, task, and action towards telehealth. The 35 respondents from Uttar Pradesh, Madhya Pradesh, Delhi, and Rajasthan. Find the results approximately 10-90% of telehealth services increase in clinical and non-clinical facilities. Approximately 95% of healthcare providers adapted telehealth delivery in the pandemic situation. The observation of preparedness in telehealth services and continued effort to address the situation by local health care providers. The status of real-time response to the prevention and control of new incidents. The role of telehealth setting in COVID-19, situation disembarrass through Voice call, text message, picture/video message, and all other possible measures were employed to accumulate maximum clinical information in real-time.